The great game of soccer - Liss, Howard. 4 0 16; Curtis, Bruce; 5 (New York : Putnam, 2004)
Traces the evolution of soccer from a rough-and-tumble free-for-all into the world's most popular spectator sport and outlines the game's rules.
Includes index.
5.7;5-8;5-8
Keywords: 2 -- 0; 6; Rules;History -- Soccer;Soccer;Soccer;Soccer. -- 20 -- Juvenile literature.;Juvenile literature.;Juvenile literature; 20; 2